A workshop on Doing Development Differently - and CID (CID at Harvard University and ODI)
October 22-23, 2014 A workshop on Doing Development Differently Harvard Kennedy School, Cambridge, MA Hosted by the Building State Capability (BSC) program at the Center for International Development at Harvard University, and the Overseas Development Institute (ODI) with funding from the Governance Partnership Facility.